If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6x = 5 + -3 + 15x Combine like terms: 5 + -3 = 2 12 + -6x = 2 + 15x Solving 12 + -6x = 2 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 12 + -6x + -15x = 2 + 15x + -15x Combine like terms: -6x + -15x = -21x 12 + -21x = 2 + 15x + -15x Combine like terms: 15x + -15x = 0 12 + -21x = 2 + 0 12 + -21x = 2 Add '-12' to each side of the equation. 12 + -12 + -21x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -21x = 2 + -12 -21x = 2 + -12 Combine like terms: 2 + -12 = -10 -21x = -10 Divide each side by '-21'. x = 0.4761904762 Simplifying x = 0.4761904762
| -5x-5=-5x | | 3(2x-5)=-39 | | 14+2x=-9-5x+4x | | 7g=49 | | y=-1/4+1 | | 3(x+3)=8x+6-5x+3 | | 9-9x=173-37x | | -2/5= | | 3x-12=4x-9 | | 5(2-y)+7y=-3(y+5) | | 3x+8=116 | | -3x+5=-3x+4 | | -3*-4*4-4*-4*-2= | | x-8=-51 | | 4y-7=3-2(9y-15) | | -6x-33=-3x-27 | | .35x+.20(240-x)=57 | | -3x-25=4(x-1) | | 8x^3-20x^2-2x+5=0 | | -6=-3+x | | 2x+6=9+3x-3 | | 8x^3-20x-2x+5=0 | | .4x+4.2=.3x+2.6 | | (2x-9)+14=(3x-8) | | 7X=10X | | 12=2(x+1)-6 | | 3(3x-3)-2=5x-43 | | 2x+1/8=5/3 | | 4(x+3)=2x+46 | | -1/4+1= | | 12+2x=42 | | -2.9c=8.7 |